2000
DOI: 10.1093/humrep/15.11.2371
|View full text |Cite
|
Sign up to set email alerts
|

Increased sperm motility after in-vitro culture of testicular biopsies from obstructive azoospermic patients results in better post-thaw recovery rate

Abstract: The objective of this study was to optimize the use of testicular biopsies in 14 patients with obstructive azoospermia. Testicular specimens were retrieved from six patients (group I) and cultured at 32 and 37 degrees C for up to 20 days; changes in percentage motile spermatozoa were compared. In four men of group I, one portion of the specimen was frozen at retrieval, and changes in post-thaw motility after 24 h of culture at 37 degrees C were recorded. In the other eight patients (group II), testicular speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
4
18
0
4
Order By: Relevance
“…We have observed the latter phenomenon in this and prior studies [5], observing a downward shift in the initial % post-thaw motility in each movement category. The IVC outcomes of this study are consistent with prior observations [5,8,9]. The more overt the movement of sperm, the easier the task at hand is for the Embryologist diligently assessing the cellular milleu to isolate viable sperm for injection.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have observed the latter phenomenon in this and prior studies [5], observing a downward shift in the initial % post-thaw motility in each movement category. The IVC outcomes of this study are consistent with prior observations [5,8,9]. The more overt the movement of sperm, the easier the task at hand is for the Embryologist diligently assessing the cellular milleu to isolate viable sperm for injection.…”
Section: Discussionsupporting
confidence: 88%
“…Initially, 5-10% twitching may be observed in a fresh specimen (0-3 hours), with the infrequent occurrence of more active sperm. It has been shown that in vitro culture (IVC) of testicular tissue does promote motility onset and progression [6,7], with an intermediate incubation temperature of 30-32ºC optimizing motility formation and longevity [5,8,9]. Although testicular sperm motility is not required to achieve fertilization by fresh sperm post-ICSI [10], it is generally considered preferential for increasing pregnancy potential [11].…”
Section: Introductionmentioning
confidence: 99%
“…China. 4 To whom correspondence should be addressed; e-mail: bwu13@ yahoo.com. sperm for ICSI is now a widely practiced technique in the treatment of men with diagnosed both obstructive and non-obstructive azoospermia.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal use of testicular biopsies for these treatments would therefore reduce surgical extractions to retrieval of a single sample. In the past few years, many groups have suggested methods to optimize the use of testicular biopsy specimens (2)(3)(4)(5)(6). Several strategies have been developed to optimally manage a testicular biopsy, including improvement of sperm motility and increasing the motile sperm recovery rate after freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Longer incubations are often necessary with spermatozoa retrieved from testicular biopsy or epididymal aspiration, presumably to stimulate in vitro maturation of the immature testicular sperm (1)(2)(3). Incubation of testicular sperm showed improved sperm motility, which peaked at 48 hours of in vitro culture (4,5). Pregnancies using testicular sperm incubated for >48 hours have been reported (6,7).…”
mentioning
confidence: 99%